EFFICIENCY OF THE EMPLOYMENT PROCESS - Mohanad Hussein Hamood Alsaraji (Scholar Express Journals, 2022)
HR is usually one step in digital transformation, and AI is now offering an opportunity to catch up. AI can help eliminate repetitive tasks, speed up talent search, reduce attrition and improve employee engagement. Algorithms train themselves to simulate human behavior and reimagine the experience of workers. Recent years have seen an increase in the number of companies outsourcing their core functions; Therefore, there are also opportunities within HR consulting. Human Resources is a very popular and highly competitive profession with graduate plans being among the most underwritten. Your level of focus on HR will vary from scheme to scheme, though some are based solely on the HR department and extend the candidate's experience to other functions such as: marketing, administration, and more. HR has a large scope for specialization and development within a particular HR function (eg: development, equality, diversity, employment, selection...etc) and with specialization comes additional responsibility and reward. Human Resources (HR) is one of the most important "assets" in your business. The people who make up your organization go a long way to success, whether they are employees, managers, consultants, or others. HR refers to recruiting and managing people, in accordance with the law, and therefore, the practice of HR requires knowledge of the laws that affect your workplace – at the federal, state, and local levels, in addition to legal compliance, HR covers the art of running your business internally.
Keywords: Efficiency; recruitment process